Stroke volume and myocardial contraction fraction in transthyretin amyloidosis cardiomyopathy: A systematic review - Matteo, Serenelli; Anna, Cantone; Federico, Sanguettoli; Daniele, Maio; Gioele, Fabbri; Beatrice, Dal Passo; Rita, Pavasini; Elisabetta, Tonet; Giulia, Passarini; Claudio, Rapezzi; Gianluca, Campo (Frontiers in Cardiovascular Medicine, 2023)
Background Cardiac amyloidosis (CA) is primarily a restrictive cardiomyopathy in which the impairment of diastolic function is dominant. Despite this, the left ventricular ejection fraction (LVEF) may be depressed in the late stage of the disease, but it poorly predicts prognosis in the earlier phases and does not represent well the pathophysiology of CA. Many echocardiographic parameters resulted important diagnostic and prognostic tools in patients with CA. Stroke volume (SV) and myocardial contraction fraction (MCF) may be obtained both with echocardiography and cardiac magnetic resonance (MRI). They reflect many factors intrinsically related to the pathophysiology of CA and are therefore potentially associated with symptoms and prognosis in CA. Objectives To collect and summarize the current evidence on SV and MCF and their clinical and prognostic role in transthyretin (TTR-CA). Methods and results We performed a systematic review following the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. We searched the literature database for studies focusing on SV and MCF in patients with TTR-CA. We analysed the following databases: PUBMED, Cochrane Library, EMBASE, and Web of Science database. Fourteen studies were included in the review. Both SV and MCF have important prognostic implications and are related to mortality. Furthermore, SV is more related to symptoms than LVEF and predicts tolerability of beta-blocker therapy in TTR-CA. Finally, SV showed to be an excellent measure to suggest the presence of TTR-CA in patients with severe aortic stenosis. Conclusion Stroke volume and MCF are very informative parameters that should be routinely assessed during the standard echocardiographic examination of all patients with TTR-CA. They carry a prognostic role while being associated with patients’ symptoms. Systematic review registration https://doi.org/10.17605/OSF.IO/ME7DS.